Sosialisasi Bahan, Produk, Proses Dan Fasilitas Halal Untuk Kantin Di Lingkungan Fakultas Teknik Universitas Hasanuddin - Muthalib, Irwan Setiawan; Mengenre, Saiful; Asmal, Sapta; M.Parenreng, Syarifuddin; Amar, Kifayah; W, Heri Bagio; ., Nurul; Setyaningrum, Ika; Melani, A.ST. Hajar; M, Maula Sidi (Faculty of Engineering UNHAS, 2023)
The year 2015 is an important point for businesses, especially in the food and beverage sector, in order to prepare materials, products, processes and facilities that are clean, healthy and safe and halal for public consumption. SMEs (Small and Medium Enterprises) are required to be more active in improving the quality of their products and services because of the implementation of the AEC (Asian Economic Community). Islam is known to be the fastest growing religion in this decade. In 2010 the number of Muslims in the world reached 1.6 billion and is expected to reach 2.2 billion by 2030 (Pew Research Center, 2011). The increase in demand for the world halal market has reached US2.3 trillion annually where halal food products alone have recorded US693 billion (MITI, 2012). For this reason, halal certification is needed. Halal certification is a process for obtaining a halal certificate through several stages of examination to prove that the ingredients, production process, and halal assurance system meet the standards of the Indonesian Ulema Council's Food, Drug and Cosmetic Assessment Institute (LPPOM MUI). The purpose of this service is to provide knowledge in the form of insight and understanding of halal toyiban ingredients, products, processes and facilities and assistance on the importance of halal certification to canteen owners in the environment around the Faculty of Engineering Unhas, Bontomarannu Gowa. The methods used in this socialization are; by conducting open meetings between partners and the academic community involved, then continued by listening to inspiration and discussion with the head of the halal assurance institution (LPH) or the Halal Assurance Center (PPH) Hasanuddin University. This socialization activity begins by giving a pre-tes to business actors to find out their initial knowledge of Halal, then at the end of the meeting a post-tes is conducted again in order to get an increase in knowledge and information and insights of business actors regarding this Halal. The results in the correct answer in the pre tes were 33% correct and in the post tes there were 67% who answered correctly. While in the wrong answer 76% were seen in the pre tes and 24% were seen wrong in the post tes. The results of socialization activities are an increase in knowledge and understanding of business actors regarding halal ingredients, products, processes, facilities due to their motivation and enthusiasm to know more about this halal product. These SMEs are already aware and understand to have halal certification, which can be used for the progress of their SME business.